Cluster structure of 9Be from many-particles reactions - V. Ostashko; M. Lattuada; M. Milin; O. Goryunov; A. Di Pietro; D. Miljanic; M. Zadro; A. Musumara; M.-G. Pellegriti; S. Romano; S. Tudisco; A. Tumino; et al. (Ядерна фізика та енергетика)
Many-particle exit channels 9 13 13 5 Be C C He (, ) α and 9 13 13 8 . . (, ) Be C C Be n g s from the 9 13 Be C + interaction have been experimentally investigated. Information has been received on 8 Be n g s. . − and 5 α − He configurations associated with 9 Be excitation states. Comparison of these configurations with calculations based on alpha-cluster conception with a valence neutron is discussed.